Work study in manufacturing with validation using Quest Simulation / Normaslina Alias - Alias, Normaslina (2004)
Increasing productivity is a big topic in appraising today. The manufacturing industries have to make improvement in order to compete in the competitive world. This project is focusing to increase productivity in manufacturing industry. Time taken at every workstation and during the model change was recorded. Current production is then simulated using Quest Simulation V5R11. The problem occur at the line was identified from the work study and customer quality report from October 2002 until September 2003. To encounter the problems, three ideas of improvement, was proposed and discussed. Selected ideas was simulated using Quest Simulation V5R11 to predict the result of the improvement. Based from the validation, the improvement is expected to increase the production rate by 12.9% compared to initial target 10% and the suggestion of improvement will have no incremental in manufacturing cost, no major changes due to the process and no effect on quality of product.